PENGARUH REVITALISASI DAN PENGGUNAAN SYSTEM TAPPING GATE TERHADAP PERAWATAN TOILET UMUM BERBAYAR DI PASAR INDUK KRAMAT JATI - Ai Nety Sumidartini; Sukarni Novitasari (UIR Press, 2021)
Perumda Pasar Jaya again held an auction for the revitalization of the maintenance and management of the Kramat Jati main market toilet, which is in Jakarta, and currently the winner of the Auction from the Revitalization of Maintenance and Management is PT. Answara Sukses Perdana Indonesia, because in this case in order to create a clean and comfortable market toilet. So that market visitors are more comfortable to enter the traditional market. The management and maintenance of toilets on the market today is constantly improving every year. This is in accordance with the slogan of Pasar Jaya which wants to create a clean and healthy market scope. Market management wants toilet cleanliness to be one of the benchmarks in seeing market feasibility.